Summertime waltz - Payne, Nina (Farrar, Straus and Giroux, 2005)
Illustrations and rhythmic text describe the delights of a summer evening. A poetic interpretation of the summer evenings of childhood Lovely the lateness in summertime darkening. Dinner is over. The grownups are talking. Seizing their moment, the children steal away from the dinner table to play out of doors, until it's too dark to see the ball and their mothers call them home. Finely wrought oil paintings, beguiling and dreamlike in their detail, give a free-spirited interpretation of the poem. Together, words and pictures evoke the lush scents, sounds, and feel of the full lingering days of summer, when outside and inside is lost in the doorways.